Respuesta :

Answer:

6.3

Step-by-step explanation:

[tex]6^{2} + 2^{2} = x^{2}[/tex]

40 = [tex]x^{2}[/tex]

[tex]\sqrt{40} = \sqrt{x^{2} }[/tex]

x = 6.3

Answer:

6.3

Step-by-step explanation:

Pythagoras' Theorem (or Pythagorean Theorem) states a²+b²=c², where c is the hypotenuse.

We can use this equation and swap a and b for 6 and 2. This gives 6²+2²=c², which can be expanded to 36+4=c², and further c²=40.

To work out c, we need to square root both sides, leaving c=6.3245553203367586639977870888654, which rounded to 1 decimal place (nearest tenth) is 6.3.

**This content involves Pythagoras' Theorem or The Pythagorean Theorem, which you may wish to revise. I'm always happy to help!